2021
DOI: 10.1111/1751-2980.13027
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of a community‐based colorectal cancer screening program in Shanghai, China

Abstract: Objective This study investigated the cost‐effectiveness of a community‐based colorectal cancer‐screening program (C‐CRCSP) in Shanghai, China, among the residents in the urban, suburban and rural areas. Methods A Markov model was constructed to evaluate the cost‐effectiveness of a 25‐year annual C‐CRCSP including 100 000 populations. Cost‐effectiveness was determined by the incremental cost‐effectiveness ratio (ICER); referring to either life‐years gained, or quality‐adjusted life‐years (QALYs) gained. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This is also currently considered as a general model for the cancer screening program in China. Furthermore, cost‐effectiveness analysis for colorectal cancer screening in Shanghai, China showed that the plan was more favorable for the rural than the urban population, primarily due to the relatively low participation rate in urban areas [ 64 , 65 ]. More and more studies have recently involved the use of circulating tumor DNA methylation profiles for the early screening or diagnosis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is also currently considered as a general model for the cancer screening program in China. Furthermore, cost‐effectiveness analysis for colorectal cancer screening in Shanghai, China showed that the plan was more favorable for the rural than the urban population, primarily due to the relatively low participation rate in urban areas [ 64 , 65 ]. More and more studies have recently involved the use of circulating tumor DNA methylation profiles for the early screening or diagnosis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The annual transition probabilities from one status to another were used as the input. For the annual transition probability of CRC, we referred to the value reported by Ren et al 11 and Li et al 12 (from non-advanced adenoma to advanced adenoma, 2%; from advanced adenoma to local cancer: 4.4%; from local to regional cancer, 30% [25–35%]; and from regional to distant cancer, 50% [45–55%]).…”
Section: Methodsmentioning
confidence: 99%